Odpowiedzi

2009-12-02T21:27:08+01:00
A)
{2x + 4y =0
{-2x - y = -1
--------------- +
3y=-1
y=-1/3

{2x + 4y =0
{-2x - y = -1 /*4

{2x + 4y =0
{-8x-4y=-4
--------------- +
-6x=4
x= - 2/3




b)
{k + l = 4
{-k + l = -3
-------------- +
2l=1
l=1/2

{k + l = 4 /*-1
{-k + l = -3

{-k -l = -4
{-k + l = -3
---------------- +
-2k=-7
k=7/2
2009-12-02T21:26:53+01:00
{2x + 4y =0
+ {-2x - y = -1
-----------------
3y = -1 / ÷3
y = - 1÷3
{y = -1÷3
{2x + 4 × (-1÷3) = 0

{y = -1÷3
{2x - 4÷3 = 0

{y = -1÷3
{2x = -4÷3

{y = -1÷3
{x = -2÷3



{k + l = 4
{-k + l = -3

2l = 1
l = 1÷2

{l = 1÷2
{k + 1÷2 = 4

{l = 1÷2
{k = 3,5

Najlepsza Odpowiedź!
2009-12-02T21:40:56+01:00
{2x + 4y =0
{-2x - y = -1
3y = -1 /:3
y= -1/3
2x +4y= 0
2x + 4*(-1/3)=0
2x+ (-4/3)=0
2x= 4/3 /:2
x= 2/3


{k + l = 4
{-k + l = -3
2l= 1/:2
l = 1/2
k+l= 4
k+1/2=4
k=4-1/2
k= 3 i 1/2